RELIABILITY AND VALIDITY TESTING OF THE PERSIAN VERSION OF THE DERRIFORD APPEARANCE SCALE 24 IN A SAMPLE OF INDIVIDUALS WITH CRANIOFACIAL IRREGULARITY AND AMPUTATION - Alireza Khani; Taher Babaee; Alireza Khaghani; Masoomeh Nakhaee; Zahra Fattahi; Timothy Moss (Canadian Prosthetics & Orthotics Journal, 2023)
BACKGROUND: Despite the recent advancements in the design and manufacture of prostheses for individuals with craniofacial irregularity and amputation, these individuals tend to become self-conscious about their appearance. The aim of this study was to investigate the reliability and validity of Persian version of the Derriford Appearance Scale24 (P-DAS24) for a sample of individuals with craniofacial irregularity and limb loss.